KAJIAN BUDIDAYA TANAMAN PALA (Myristica fragrans Houtt) DI KABUPATEN KEPULAUAN SANGIHE - Widia L. Legoh; Deanne Kojoh; Semuel Runtunuwu (COCOS, 2017)
ABSTRACT This study aims to determine the nutmeg crop cultivation techniques carried out by farmers in Sangihe Islands Regency. This research is a quantitative data of collection techniques using a structured questionnaire to collect data on the cultivation of nutmeg applied by farmers, from seeding to the control of pests and diseases. Farmers surveyed 150 people, divided into three sub-district in the District of West Tahuna, Manganitu and Kendahe.Â  Determination of farmers in every village performed by using the "purposive sampling" or intentionally sampling based on the presence or absence of inputs received assistance. The results showed that the nutmeg crop cultivation practices applied by farmers in the district of Sangihe is still not in accordance with good farming techniques, such as the preparation of seedlings, fertilization and pest control.Keywords: Study, Cultivation, Nutmeg Plant, Sangihe